Causes of Maternal Mortality and Its Implications for Adult Education in Nsukka Local Government Area of Enugu State - Mercy Okeke, Nkechi; G. Ozurumba, Iheanyichukwu; Ngozi , F. Nnaji (International Journal of Psychosocial Rehabilitation, 2021)
The study investigated the causes of maternal mortality in Nsukka Local Government Area of Enugu State, Nigeria and its implication for adult education. One research question was used to determine the causes of maternal mortality. The survey design was used. Data was collected using a questionnaire. A total of 108 pregnant women participated in the study. Data were analyzed using mean and standard deviation. The study revealed that hypertensive disorder of pregnancy, unsafe abortion and obstructed labour were among the highest causes of maternal mortality. Based on the study findings, the following recommendations were made: government should organize health education campaign for pregnant women in their communities; women should reduce the number of childbirth; and women should avail themselves of health care services such as family planning, emergency obstetric care and intrapartum care